Penerapan Model Pembelajaran Inkuiri (Inquiry Learning) untuk Meningkatkan Keterampilan Siswa pada Mata Pelajaran Matematika - Oktaviana, Dinda (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2025)
This study aims to improve students' skills through the application of inquiry learning models to class X MIPA students at MA Swasta Darul Hijroh in the 2024/2025 academic year in mathematics. This research is a Classroom Action Research (CAR). The research was carried out in two cycles consisting of planning, implementing actions, observing, and reflecting. The population in this study were all class X MIPA students at MA Swasta Darul Hijroh. The sampling technique used was saturated sampling or total sampling which is a sampling technique with all members of the population being sampled, and class X MIPA was obtained as a sample in the study. The data collection technique used a skills observation rubric. The results of data analysis showed that the application of the inquiry learning model increased the average value of students' skills in mathematics, which was 60 in cycle I to 84 in cycle II in the very good category. Thus, it can be concluded that the application of the inquiry learning model can improve students' skills in mathematics for class X MIPA at MA Swasta Darul Hijroh.